The influence of landscape characteristics and home-range size on the quantification of landscape-genetics relationships - Graves, Tabitha A.; Wasserman, Tzeidle N.; Ribeiro, Milton Cezar [UNESP]; Landguth, Erin L.; Spear, Stephen F.; Balkenhol, Niko; Higgins, Colleen B.; Fortin, Marie-Josee; Cushman, Samuel A.; Waits, Lisette P. (Springer, 2012)
A common approach used to estimate landscape resistance involves comparing correlations of ecological and genetic distances calculated among individuals of a species. However, the location of sampled individuals may contain some degree of spatial uncertainty due to the natural variation of animals moving through their home range or measurement error in plant or animal locations. In this study, we evaluate the ways that spatial uncertainty, landscape characteristics, and genetic stochasticity interact to influence the strength and variability of conclusions about landscape-genetics relationships. We used a neutral landscape model to generate 45 landscapes composed of habitat and non-habitat, varying in percent habitat, aggregation, and structural connectivity (patch cohesion). We created true and alternate locations for 500 individuals, calculated ecological distances (least-cost paths), and simulated genetic distances among individuals. We compared correlations between ecological distances for true and alternate locations. We then simulated genotypes at 15 neutral loci and investigated whether the same influences could be detected in simple Mantel tests and while controlling for the effects of isolation-by distance using the partial Mantel test. Spatial uncertainty interacted with the percentage of habitat in the landscape, but led to only small reductions in correlations. Furthermore, the strongest correlations occurred with low percent habitat, high aggregation, and low to intermediate levels of cohesion. Overall genetic stochasticity was relatively low and was influenced by landscape characteristics.
Keywords: Least cost; Habitat resistance; Fragmentation; Genetic structure; Sampling error; Aggregation; Cohesiveness; Connectivity; Gene flow; Isolation-by-resistance